Pengenalan Makanan Bergizi Melalui Game Edukasi Untuk Anak Usia 6-9 Tahun - Jimmy Moedjahedy; Jessica Sabbathiny Buyung; Jay Idoan Sihotang (Electro Luceat, 2022)
The health of a country is the most important measure of its overall well-being. Children are the nation's next generation, and they must be kept in good physical condition. According to the Minister of Health of the Republic of Indonesia's regulation on health, children have the right to survive and develop normally. According to a report by the Ministry of Health of the Republic of Indonesia, malnutrition and malnutrition status affect children and toddlers in particular areas. Children's misunderstanding about healthy and nutritious food contributes to the high incidence of malnourished children. As a result, the goal of this research is to create an educational game that will introduce healthful foods to children aged 6 to 9. The Waterfall Model is the software engineering approach that was employed, with the following stages of implementation: feasibility research, requirement analysis, design and specification, coding and module testing, integration and system testing, delivery and maintenance. It is believed that the findings of this study would allow youngsters to learn about nutrition through fun and instructive activities.